2017
DOI: 10.1002/cncr.30688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of depression before breast cancer diagnosis on mortality among postmenopausal women

Abstract: Condensed abstract Women with newly developed depression before the diagnosis of breast cancer had a modestly but significantly increased risk for death from any cause and death from breast cancer if diagnosed at late stage. The results also highlight the importance of prevention efforts to support mental health and prevent initial emergence of depression among older women. Background Few previous studies investigating depression before breast cancer diagnosis and breast cancer specific mortality have examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 18 publications
(40 reference statements)
4
34
0
Order By: Relevance
“…Twenty-eight studies were included in this review and 24 in the meta-analysis (figure 1). Twenty-three studies were identified from 2381 possible MEDLINE citations6–11 13 17 39–53 and an additional five articles were identified through the PubMed search and a manual search of narrative review references 12 16 18 19 54. Sixteen studies investigated stage at diagnosis and 25 investigated survival.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-eight studies were included in this review and 24 in the meta-analysis (figure 1). Twenty-three studies were identified from 2381 possible MEDLINE citations6–11 13 17 39–53 and an additional five articles were identified through the PubMed search and a manual search of narrative review references 12 16 18 19 54. Sixteen studies investigated stage at diagnosis and 25 investigated survival.…”
Section: Resultsmentioning
confidence: 99%
“…It seems that similar findings are found in patients having diagnosis of Major depressive disorder before discovering their cancer breast. Such consistent findings encouraged many authors to recommend therapeutic approach to depressive symptoms weather antidepressant medications or psychological interventions such as meditation and CBT psychotherapy [5].…”
Section: Introductionmentioning
confidence: 89%
“…Possible explanations for these findings include delayed diagnosis and lack of access to screening, which lead to more advanced staging at the time of diagnosis, and reduced access to or use of appropriate treatments after diagnosis. For example, people with depression are less likely to receive routine cancer screening (Carney and Jones, 2006), which may result in more advanced disease at presentation (Liang et al, 2017). On the other hand, some studies have documented a reduced incidence of cancer in patients with dementia and schizophrenia (Attner et al, 2010; Bushe and Hodgson, 2010; Kisely et al, 2013).…”
Section: Discussionmentioning
confidence: 99%